Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-12T17:47:25+01:00
-1/2x³y-2/3xy=1/2x³-1/3xy
-3/6x³y-4/6xy=3/6x³-2/6xy
xy(-3/6x²-4/6)=x(3/6x²-2/6y)
1/3*9(-3/6*1/9-4/6)=1/3(3/6*1/9-2/6*9)
3(-1/18-12/18)=1/3(1/18-1/18)
3*-13/18=0
39/18=0

1 5 1
2010-02-12T17:51:24+01:00
B)-1/2x³y-2/3xy=1/2x³-1/3xy

-1/2x³y - 1/2x³ = 2/3xy -1/3xy
-1/2x³y - 1/2x³ = 1/3xy
-1/2 * (1/3)³ * 9 - 1/2 * (1/3)³ = 1/3 * 1/3 * 9
-1/2 * 1/27 * 9 - 1/2 * 1/27 = 1
1/6 - 1/54 = 1
1 5 1
2010-02-12T23:24:04+01:00
B)
-½x³y-⅔xy=½x³-⅓xy
-½x³y-½x³=⅓xy
-½*(⅓)³*9 - ½*(⅓)³=⅓*⅓*9
-½*1/27*9 -½*1/27=1/9*9
-1/54*9 - 1/54 = 1
-1/6 - 1/54 = 1
-10/54 = 1





1 3 1